2011
DOI: 10.1186/1471-2296-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy for Stress-related mental disorder, a randomised controlled trial in primary care

Abstract: Backgroundto investigate whether a structured physical exercise programme (PEP) improves the recovery of general health in patients suffering from Stress-related Mental Disorder (SMD).MethodStudy design: randomised open trial in general practice. Patients from two regions in the Netherlands were included between September 2003 and December 2005, and followed up for 12 weeks.Intervention: the patients were referred to a physical therapist for instruction in and monitoring of physical exercise of an intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Our findings indicate that exercise levels can be increased in patients suffering from stress‐related exhaustion disorder (Quartero et al . ). Stress‐related exhaustion and many other mental disorders are characterised by low physical and mental energy levels and low motivation as mentioned in the introduction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our findings indicate that exercise levels can be increased in patients suffering from stress‐related exhaustion disorder (Quartero et al . ). Stress‐related exhaustion and many other mental disorders are characterised by low physical and mental energy levels and low motivation as mentioned in the introduction.…”
Section: Discussionmentioning
confidence: 97%
“…Exposure to stress precedes many mental disorders (Quartero et al . ), and previous studies have shown that increased stress levels are associated with lower levels of self‐initiated exercise (Schnohr et al . ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation